Implementación de mejoras a la plataforma de virtualización de servidores de la SUNAT - Palomino Rodríguez, Luis (2018)
The company on which the present project was carried out is a Peruvian state entity that is in charge of administering the internal taxes of the National Government. The objective of the project is to increase the hardware processing capabilities of the server virtualization platform of this entity, to reduce response times in its main information systems SIGA, SIAF and SIGED, improve its availability and speed in the solution of support cases. For this objective, the entity was putting out to tender this project, a tender won by the IBM del Peru company in February 2016. This project had a maximum finish established by the Tender Conditions of 165 days, which can be reduced to 141 days with the respective compliance of the entity. To achieve this, there was a budget for the purchase of equipment, purchase of software, training and contracting of specialized suppliers and manufacturers, and the amount for that was S / 6,131,501.78. The development of the project was based on the adjusted schedule to which IBM was committed and several meetings of agreements had to be held with the entity to be able to reach the deadlines and be in benefit of both parts. Therefore, a fine tracking of the delivery and configuration of equipment and licenses was made, to the presentations of the initial revision of the state of the server virtualization platform of the entity, the new design of the same, its implementation and tests, as well as the training offered in the proposal. Within this, there were problems that could delay the final delivery of the project and that could be corrected based on negotiation, management support and technical skills of the collaborators involved. Finally, to be able to have a correct and successful management of tenders with the state, it is a priority to be clear about the total scope of the Bases and to ask the right questions at the moment of the process that opens to consultations to ensure a successful implementation, differentiating itself from the competition. It should also consider the definition of the list of deliverables with the entity and the form of how compliance will be assessed as it is a requirement for compliance and therefore the payment of the contract.